Methods of assessment of operating effectiveness of the Intellectual information and analytical system of Occupational safety management at pharmaceutical іndustry enterprises - Siryk, Alina; Evtushenko, Olga; Lych (Tkachenko), Inna; Soloshenko, Kateryna (My University, 2019)
The article overlooks methodology for evaluating the effectiveness of the intellectual information-analytical system of labor protection management at the enterprises of the pharmaceutical industry. The introduction of this technique at the enterprises of the pharmaceutical industry in the traditional procedures of internal audit will achieve a new quality of functioning of automated information-analytical systems of labor protection management and significantly increase the efficiency of information processing in decision-making processes due to the efficiency and accuracy of choosing the optimal set of measures for ensuring safety.
Keywords: safety; labor protection; labor; information-analytical system; безпека; праця; охорона праці; інформаційно-аналітична система; кафедра екології та екоменеджменту